2020
DOI: 10.1007/s00062-020-00893-3
|View full text |Cite
|
Sign up to set email alerts
|

Different Rescue Approaches of Migrated Woven Endobridge (WEB) Devices: an Animal Study

Abstract: Purpose Treatment of wide-necked intracranial aneurysms using the Woven Endobridge (WEB) device has become broadly accepted. Feared complications with the potential of increased poor clinical outcome include dislocations and migration of the device. This study was carried out to determine the effectiveness of a variety of different strategies to rescue migrated WEB devices. Methods In a porcine model, WEB devices of different sizes (SL [single layer] 3.5 × 2mm and SL 4.0 × 3 mm, SL 8 × 5 mm and SLS 8 mm [singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…14 Other techniques have been reported for rescue maneuvers of malpositioned and migrated WEB devices in porcine models, such as the use of stent-retrievers, aspiration catheters, and rescue devices. 15,16 In our case, several intra-procedural bailout interventions were considered, although many were precluded given our patient's subarachnoid hemorrhage. Our case is unique, as it is the first reported WEB bailout strategy for an acutely ruptured aneurysm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…14 Other techniques have been reported for rescue maneuvers of malpositioned and migrated WEB devices in porcine models, such as the use of stent-retrievers, aspiration catheters, and rescue devices. 15,16 In our case, several intra-procedural bailout interventions were considered, although many were precluded given our patient's subarachnoid hemorrhage. Our case is unique, as it is the first reported WEB bailout strategy for an acutely ruptured aneurysm.…”
Section: Discussionmentioning
confidence: 94%
“…We decided against a direct aspiration first pass technique (ADAPT)-removal/repositioning with a thrombectomy aspiration catheter (which has been described in animal models). 15 We feared crossing the neck with such a large catheter, as well as exacerbating the inward-concavity of malpositioning. Furthermore, the reports of ADAPT-retrieval of WEB devices were done in porcine models where the device was positioned perpendicular to the parent artery, a situation very different than ours.…”
Section: Discussionmentioning
confidence: 99%
“…A recent animal study has shown promising results in rescuing migrated small WEBs using reperfusion catheters and larger WEBs using dedicated rescue devices such as a Microsnare and an ARD. 25 So far, stent retrievers have not been investigated in the rescue approach of WEB devices. Since 2015, mechanical thrombectomy with retrievable stents has become a standard therapy of ischemic stroke due to large vessel occlusion with very good clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed porcine vessels have similar diameters to human vessels. However, wall structures and tortuosity are different, which means that it is not possible to recreate maximally realistic scenarios [ 10 , 18 ]. A major limitation of our study was that the used swine breed, German Landrace, has not yet been widely used in neuroendovascular trials.…”
Section: Limitationsmentioning
confidence: 99%
“…Porcine animal models have gained increasing popularity due to similar anatomical, hemodynamic, and hemostatic conditions to humans [ 8 ]. Their body size allows the insertion of human standard-sized devices [ 9 , 10 ]. The porcine internal carotid artery passes through the rete mirabile, which is an anatomical characteristic of this model [ 8 ].…”
Section: Introductionmentioning
confidence: 99%